Sex-dependent gene co-expression in the human body - Robin J. G. Hartman (Nature Portfolio, 2021)
Abstract Many pathophysiological mechanisms in human health and disease are dependent on sex. Systems biology approaches are successfully used to decipher human disease etiology, yet the effect of sex on gene network biology is mostly unknown. To address this, we used RNA-sequencing data of over 700 individuals spanning 24 tissues from the Genotype-Tissue Expression project to generate a whole-body gene co-expression map and quantified the sex differences per tissue. We found that of the 13,787 genes analyzed in 24 tissues, 29.5% of the gene co-expression is influenced by sex. For example, skeletal muscle was predominantly enriched with genes co-expressed stronger in males, whereas thyroid primarily contained genes co-expressed stronger in females. This was accompanied by consistent sex differences in pathway enrichment, including hypoxia, epithelial-to-mesenchymal transition, and inflammation over the human body. Furthermore, multi-organ analyses revealed consistent sex-dependent gene co-expression over numerous tissues which was accompanied by enrichment of transcription factor binding motifs in the promoters of these genes. Finally, we show that many sex-biased genes are associated with sex-biased diseases, such as autoimmunity and cancer, and more often the target of FDA-approved drugs than non-sexbiased genes. Our study suggests that sex affects biological gene networks by differences in gene co-expression and that attention to the effect of sex on biological responses to medical drugs is warranted.